(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article examines the legal nature of the formation of courts and judicial power, from ancient times to the present. The analysis of various interpretations of the concept of “court”, “justice” and “judicial power”, which reveal its essential content, is carried out. A historical review of the emergence of the theory of separation of powers in the state as the basis for the separate functioning of the judiciary is carried out. The article examines the main characteristic features of the judiciary, on the basis of which its definition is given as a relatively independent branch of state power. Important events that have had a significant impact on the further development of the judicial power of democratic states are noted.